World Map Media Improves Country Identification Skills in Elementary Students: World Map Media Meningkatkan Kemampuan Identifikasi Negara pada Siswa Sekolah Dasar - Fadilah Eka Febriani; Widyastuti Widyastuti (Academia Open, 2025)
General Background: Geography learning in elementary education requires concrete visual media to support students’ spatial understanding and country identification skills. Specific Background: Conventional instructional approaches often limit students’ engagement and accuracy in recognizing countries on a world map. Knowledge Gap: Despite the availability of various visual learning tools, structured implementation of World Map–based media for systematic country identification learning remains underexplored in elementary classroom contexts. Aims: This study aims to examine student learning outcomes after the application of World Map–based media in teaching country identification. Results: The findings demonstrate measurable improvement in students’ ability to recognize and correctly identify countries, as reflected in increased post-instruction scores compared to prior performance. Students showed better spatial recognition and map-reading accuracy during the learning process. Novelty: The study introduces a structured classroom application of physical World Map media specifically designed for country identification tasks at the elementary level. Implications: These findings contribute to geography education practices by supporting the integration of visual-spatial instructional media to facilitate more interactive and meaningful learning experiences in elementary social studies classrooms. Keywords: World Map Media, Country Identification, Geography Learning, Elementary Education, Visual Learning Key Findings Highlights: Students demonstrated higher post-instruction achievement in recognizing global locations. Classroom activities showed improved spatial orientation accuracy. Visual map-based instruction supported more active student participation.